Itraconazole promotes melanoma cells apoptosis via inhibiting hedgehog signaling pathway-mediated autophagy - Jin, Shunqiao; Liu, Xiaojiao; Cai, Lingqin; Yan, Jiayu; Li, Ling; Dong, Hongjun; Gao, Yuxue; Zhu, Xicong; Zhang, Cong; Xu, Xuezhu (Frontiers in Pharmacology, 2025)
BackgroundItraconazole, a widely used antifungal medication, has shown potential in inhibiting tumor growth and reducing angiogenesis. However, its role in melanoma tumor growth remains insufficiently explored. This study investigates the inductive effect of itraconazole on autophagy-mediated apoptosis in melanoma cells.MethodPotential drug targets were identified using the PMF machine learning algorithm. Apoptosis and cell cycle in melanoma cell lines A375 and A2058 were assessed via flow cytometry. Western blot analysis was performed to examine autophagy and associated signaling proteins, while autophagy flux and autophagosome formation were visualized using fluorescence microscopy. A melanoma cell xenograft mouse model was established to evaluate the inhibitory mechanisms of itraconazole on tumor cell proliferation.ResultUsing the PMF machine learning algorithm, SQSTM1 was identified as the primary target of itraconazole. Itraconazole inhibited melanoma cell proliferation by inducing G1 phase arrest and autophagy-mediated apoptosis in A375 and A2058 cells. Furthermore, itraconazole suppressed Hedgehog signaling and counteracted the activation of the Hedgehog agonist recombinant human Sonic Hedgehog (rhShh). In vivo, itraconazole significantly reduced tumor growth in A375 and A2058 xenograft models.ConclusionItraconazole induces autophagy-mediated apoptosis in melanoma cells by inhibiting Hedgehog signaling, underscoring its potential as a therapeutic option for melanoma treatment.